Rancang Bangun Alat Monitoring Penggunaan Air Pamsimas Berbasis Arduino Di Desa Sekartejo - Erman Al Hakim; Arba'i Yusuf; Rosyid, Muhail (Politeknik Piksi Ganesha Indonesia, 2021)
The PAMSIMAS program is one of the government initiatives aimed at facilitating the water and sanitation needs of rural communities. One such PAMSIMAS program is implemented in the village of Sekartrjo, known as PAMSIMAS SEKAR TIRTA. The calculation of water prices and usage from PAMSIMAS is currently done manually, which is inefficient in terms of time and effort for the PAMSIMAS management. The objective of this research is to simplify the calculation of water prices and usage for PAMSIMAS management by creating an